2016
DOI: 10.2183/pjab.92.346
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of memory-guided choice behavior in <i>Drosophila</i>

Abstract: Memory retrieval requires both accuracy and speed. Olfactory learning of the fruit fly Drosophila melanogaster serves as a powerful model system to identify molecular and neuronal substrates of memory and memory-guided behavior. The behavioral expression of olfactory memory has traditionally been tested as a conditioned odor response in a simple T-maze, which measures the result, but not the speed, of odor choice. Here, we developed multiplexed T-mazes that allow video recording of the choice behavior. Automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Further functional dissections revealed that different subpopulations of DANs and MBONs encode information regarding the sweet vs. caloric value of the ingested food (Das et al, 2014 ), water reward (Shyu et al, 2017 ), aversive taste (Masek et al, 2015 ), electric shock memory (Unoki et al, 2005 ; Aso et al, 2010 ), and even specific short and long-term memory formation (Aso et al, 2014b ). Memory formation, consolidation, retrieval, reconsolidation and/or extinction have been shown to occur via neuronal activities in specific parts of the MBONs and specific subsets of reinforcing DANs (Berry et al, 2012 , 2015 ; Shuai et al, 2015 ; Aso and Rubin, 2016 ; Ichinose and Tanimoto, 2016 ) reviewed by Cognigni et al ( 2018 ). Intriguingly, re-evaluation of previously learned appetitive memory was shown to be conveyed by the activity of a subset of MBONs that is anatomically connected to both aversive and appetitive DANs, and that extinction or re-consolidation of appetitive memories requires activity of both during re-evaluation (Felsenberg et al, 2017 ).…”
Section: Drug-unrelated Studies and Their Contribution To Understandimentioning
confidence: 99%
“…Further functional dissections revealed that different subpopulations of DANs and MBONs encode information regarding the sweet vs. caloric value of the ingested food (Das et al, 2014 ), water reward (Shyu et al, 2017 ), aversive taste (Masek et al, 2015 ), electric shock memory (Unoki et al, 2005 ; Aso et al, 2010 ), and even specific short and long-term memory formation (Aso et al, 2014b ). Memory formation, consolidation, retrieval, reconsolidation and/or extinction have been shown to occur via neuronal activities in specific parts of the MBONs and specific subsets of reinforcing DANs (Berry et al, 2012 , 2015 ; Shuai et al, 2015 ; Aso and Rubin, 2016 ; Ichinose and Tanimoto, 2016 ) reviewed by Cognigni et al ( 2018 ). Intriguingly, re-evaluation of previously learned appetitive memory was shown to be conveyed by the activity of a subset of MBONs that is anatomically connected to both aversive and appetitive DANs, and that extinction or re-consolidation of appetitive memories requires activity of both during re-evaluation (Felsenberg et al, 2017 ).…”
Section: Drug-unrelated Studies and Their Contribution To Understandimentioning
confidence: 99%
“…Specifically, flies in behavioral chambers (as used here) are in constant motion, so that they repeatedly enter and exit the odor plume, and make multiple decisions each time 54,60,61 . In contrast, flies in the T-maze (as used in 15 ) make fewer decisions and reach steady state more rapidly 62 . Another difference is that flies in a T-maze make their decision within 3-4 seconds 63 , whereas the standard analysis of the behavioral chambers takes into account a two minute window with repeated decisions 54,60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…We created a revised T-maze apparatus specialized for silkworm experiments. Following previous efforts [ 21 ], the device had two channels leading to a reward and punishment, respectively. There were two rooms in each channel.…”
Section: Methodsmentioning
confidence: 99%